Spontaneous regression of primary cutaneous diffuse large B-cell lymphoma, leg type: a case series and review of the literature - Winkler, Manuel; Albrecht, Jana Dorothea; Sauer, Christian; Kordaß, Theresa; Guenova, Emmanuella; Livingstone, Elisabeth; Wobser, Marion; Mitteldorf, Christina; Géraud, Cyrill; Nicolay, Jan Peter (The journal of dermatology, 2024)
Primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL, LT) is a subtype of cutaneous B-cell lymphoma with unfavorable prognosis usually requiring aggressive polychemotherapy for disease control. Only single cases of spontaneous regression of PCDLBCL, LT are reported in the literature, peaking 3 months post-biopsy following a clinical history of no longer than 1 year. Here, we report the first case of a spontaneously relapsing and remitting PCDLBCL, LT with complete regression after a clinical history of more than 9 years and thus an atypically indolent clinical course. The female patient presented with recurrent erythematous, non-ulcerated, non-raised plaques of the right lower leg for 6 years. Pathological workup and exclusion of a systemic disease confirmed the diagnosis of PCDLBCL, LT. Due to the history of repeated spontaneous remission, no therapy was initiated. Nine years after first occurrence the patient presented with complete clinical remission lasting for 64 months. We retrospectively identified four additional PCDLBCL, LT patients with spontaneous remission lasting up to 53 months. Our data provide evidence for a distinct PCDLBCL, LT patient subgroup that clinicians should be aware of and warrants a watch-and-wait treatment regime.